2018
DOI: 10.1002/cctc.201800987
|View full text |Cite
|
Sign up to set email alerts
|

Aminal‐based Hypercrosslinked Polymer Modified with Small Palladium Nanoparticles for Efficiently Catalytic Reduction of Nitroarenes

Abstract: Fabrication of heterogeneous catalysts with excellent activity, selectivity and stability is significant for various catalytic applications. Here, we prepared a hypercrosslinked polymer (HCP) via a facile and cost‐effective strategy using ferrocenecarboxaldehyde and melamine as building blocks. Then, the HCP was modified with highly dispersed ultrafine Pd nanoparticles (Pd/HCP). The obtained Pd/HCP shows excellent catalytic activity in the catalytic reduction of nitroarenes under mild reaction conditions. It′s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…92 Dong et al prepared thiol-containing HCPs using ferrocenecarboxaldehyde and melamine as building blocks, which were loaded with Pd UMNPs (2.89 nm). 93 The resulting Pd UMNPs@HCPs composites showed excellent activity and stability in the catalytic reduction of nitroarenes. Tan et al reported a series of Au UMNPs (range of 1.7 -5.1 nm) supported on a HCP (Figure 12b).…”
Section: Synthesis Of Umnps Supported By Amorphous Organic Polymersmentioning
confidence: 99%
“…92 Dong et al prepared thiol-containing HCPs using ferrocenecarboxaldehyde and melamine as building blocks, which were loaded with Pd UMNPs (2.89 nm). 93 The resulting Pd UMNPs@HCPs composites showed excellent activity and stability in the catalytic reduction of nitroarenes. Tan et al reported a series of Au UMNPs (range of 1.7 -5.1 nm) supported on a HCP (Figure 12b).…”
Section: Synthesis Of Umnps Supported By Amorphous Organic Polymersmentioning
confidence: 99%
“…Finally, changing the nature of the solvent was unsuccessful since low yields were observed in iPrOH or propane-1,2-diol and no reaction was observed in H 2 O (entries 9-11). It can be pointed out that, compared to numerous catalysts and reducing agents described, [15][16][17][18] both IM1 and IM2 allowed a chemospecic reduction of the nitro group (the acetyl remaining unchanged) and avoided the necessity of high H 2 pressure. Interestingly, performing the hydrogenation in the presence of a commercially available Pd/C or of Pd Encat NP30 catalyst afforded 1a in much lower yields (entries 12 and 13) conrming therefore the high activity of IM2.…”
Section: Activity Of Catalysts Im1-im3 and Dm For Hydrogenations Of Nmentioning
confidence: 99%
“…To investigate applicability of our catalyst in a flow process [116][117][118][119][120], we simulated a flow reactor with a simple proof-of-concept model. Catalyst Co@350 was loaded onto two 0.22 µm nylon syringe filters; 8 mg in filter (i) and 4 mg in filter (ii), then stacked sequentially ( Figure 8A).…”
Section: Testing Applicability Of Co@350 In a Flow Processmentioning
confidence: 99%